Faire voir l'Orient : réflexion sur un artifice victorien - Laurent Bury (Sillages Critiques)
As part of the Western construction of an Eastern myth, painting was very soon mobilized to support written texts, so as to offer images which now appear to be more informative on their creators (and on their audiences) than on the realities they claimed to document. One of the “imposed figures”of the extended Grand Tour, the harem, was painted by J.F. Lewis and photographed by R. Fenton, whose works clearly reveal the artificiality of their subject. Victorian Orientalism also implied a “re-orientalisation” of the Christian myth; artists as diverse as David Wilkie or William Holman Hunt were motivated by their quest for authenticity, even though the racist prejudice then prevalent had to be taken into account. A vision of the East was thus elaborated to fit the expectations of the public, a vision that was aesthetically more satisfactory than would have been a faithful reproduction of reality.